2013
DOI: 10.1017/jfm.2013.78
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of parametric subharmonic instability for internal plane waves

Abstract: Internal waves are believed to be of primary importance as they affect ocean mixing and energy transport. Several processes can lead to the breaking of internal waves and they usually involve non linear interactions between waves. In this work, we study experimentally the parametric subharmonic instability (PSI), which provides an efficient mechanism to transfer energy from large to smaller scales. It corresponds to the destabilization of a primary plane wave and the spontaneous emission of two secondary waves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
139
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(164 citation statements)
references
References 34 publications
22
139
3
Order By: Relevance
“…having prominent peaks at the forcing frequency, ω 0 ≈ 1.03 s −1 , as well as at ω 1 ≈ 0.73 s −1 and ω 2 ≈ 0.31 s −1 , corresponding to the two daughter waves. These frequency peaks satisfy the resonance condition ω 0 = ω 1 + ω 2 to within 1%, thus confirming the formation of a resonant wave triad; the spatial resonance condition, which is a well established experimental feature, 13,14 was also checked and confirmed. The relatively high forcing frequency results in steeply oriented constant phase lines for the forced wave field, which in turn yields strong and weak vertical and horizontal velocities, respectively.…”
Section: -4 Ghaemsaidi Et Alsupporting
confidence: 66%
See 1 more Smart Citation
“…having prominent peaks at the forcing frequency, ω 0 ≈ 1.03 s −1 , as well as at ω 1 ≈ 0.73 s −1 and ω 2 ≈ 0.31 s −1 , corresponding to the two daughter waves. These frequency peaks satisfy the resonance condition ω 0 = ω 1 + ω 2 to within 1%, thus confirming the formation of a resonant wave triad; the spatial resonance condition, which is a well established experimental feature, 13,14 was also checked and confirmed. The relatively high forcing frequency results in steeply oriented constant phase lines for the forced wave field, which in turn yields strong and weak vertical and horizontal velocities, respectively.…”
Section: -4 Ghaemsaidi Et Alsupporting
confidence: 66%
“…Complementary laboratory studies in uniform stratifications have demonstrated conditions under which internal wave fields become unstable to minute perturbations via PSI. 13,14 In this letter, we present the results of a laboratory experiment in which internal waves are excited in a relatively shallow, upper layer of high buoyancy frequency, N 1 , sitting atop a deeper layer of low buoyancy frequency, N 2 . The internal wave field is excited at a relatively high frequency ω 0 (i.e., N 2 < ω 0 < N 1 ) via boundary forcing imposed at the top of the upper layer; as such, the wave field excited at the forcing frequency is confined to the upper layer because it is evanescent in the lower layer.…”
mentioning
confidence: 99%
“…One breakthrough of Bourget et al (2013) is the use of a new wave generation mechanism that creates a beam with three across-beam wavelengths spanning its width. Thus they are able to observe the onset of instability in the beam, as shown in figure 1(e,f ).…”
Section: Overviewmentioning
confidence: 99%
“…The other breakthrough of Bourget et al (2013) is the application of novel analysis methods that separate the signal of the primary beam and the subharmonic waves it excites. For example, at an arbitrary point in the tank measurements of the perturbation vertical density gradient versus time can be Fourier transformed.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation